Challenges and Coping Strategies of EFL Trainee Teachers in International Teaching Practicum - Khusniyah, Zalfa Amirah; Shahrom, Syahreena Mohd; Elfiyanto, Sonny; Hidayanti, Ika (VELES Voices of English Language Education Society, 2023)
International teaching practicum is highly relevant in developing the quality of education worldwide. Innumerable institution sends their trainee teachers to help improve educational quality and build professionalism. During the practicum, trainee teachers will be experiencing some pertinent issues and problems that will help to shape teachers’ personalities and teaching practices in the future. Knowing the importance of experiencing these challenging episodes in practicum, researchers investigated the coping strategies for challenges and reported how trainee teachers conceptualized their learning. This qualitative research aims to provide valuable insight and practical solutions for trainee teachers facing challenges during teaching practicum. The data was obtained through observation and interviews with two trainee teachers who have participated in an international teaching practicum in Malaysia. Based on the research finding, the challenges faced by trainee teachers are categorized into several themes: students’ behavior, school facilities, mixed-ability students, school curriculum, and time management. Moreover, trainee teachers used several coping strategies to overcome challenges: antecedent strategy; learning through play strategy; grouping strategy; school modules to overcome unfixed curriculum; and setting priorities.